'There is a shark coming, then there is a du-du-du-du-du…': Mediating cultural tools in a Norwegian creative music-making project. Issue 2 (31st May 2019) - Viig, Tine Grieg
Abstract: This article reports on a case study in a Norwegian primary school where nearly 50 fifth-grade pupils took part in a creative music-making project. Facilitated by two professional artists, they created an original piece of music and performed their composition for an audience at the end of the project week. A substantial part of the data consisted of recorded sounds, notations, transcribed interviews and documentations of the process of music composition from the first ideas to the final performance. The analysis was conducted from a sociocultural perspective with a special focus on the mediating tools used in the community of creative musical practice. The findings suggest that the cultural tools used in the project were dynamic and interactive, employed by both the facilitators and the participants. The mediating tools found in the creative music making make up a complex toolbox the participants share and develop, consisting of both psychological and material tools. There were three main categories of mediating tools identified. First, the use of symbolic signs, such as graphic notation, was important from the initial stages when the participants developed musical ideas to the final performance. Second, the actions and interactions of music making, such as conducting gestures shared and developed through the project, were both founded on traditional conductor signs but also transformed and adapted to new ways of mediating musical meaning in this particular project. Third, the participants worked with 'creative reworkings' of experiences in this project. Through the transformation of previous experiences into the creation of new musical material, important mediating tools were identified as experiences and meaning in the creative musical practice.